Variasi Morfologi Dan Anatomi Sukun (Artocarpus altilis) Berdasarkan Perbedaan Ketinggian Tempat - Dian Palupi; Riska Desi Aryani; Sri Lestari (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Breadfruit [Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg] is a versatile plant that can be used by humans. Breadfruit has morphological variations that are thought to be related to anatomical variations that are formed as an adaptation mechanism to survive in a different area. This plant has the ability to live in different altitude ranges, from coastal areas to upland areas. This research was conducted for eight months in areas with altitude ranges of <350 masl, 350-700 masl, and >700 masl in Banyumas, Purbalingga, and Cilacap Regencies. Sampling of plants was carried out randomly selected (purposive random sampling), then described their morphological characteristics. Furthermore, the leaves are made for anatomical preservation to determine the anatomical character. Breadfruit plants that grow at an altitude of less than 350 m above sea level have the characteristics of a higher, larger diameter stem, have a tighter branching, more sap production, a higher number of fruit and have a larger fruit size. The anatomical characteristics of breadfruit plants that grow at an altitude of less than 350 masl have stomata characters that are wider and longer than those of 350-700 masl and > 700 masl. The highest stomata and trichomata density at an altitude > 700 masl. The highest mean cuticle thickness, epidermis, palisade ratio and mesophyll thickness were highest in breadfruit leaves at altitudes <350 masl.